On some relations of SCA-related properties of S-box under the Hamming weight leakage mode - Echevarría, Alejandro Freyre; Aulet, Ramses Rodríguez; Gómez, Alejandro García (Journal of Science and Technology on Information security, 2023)
Abstract— Physical implementations of cryptographic algorithms are vulnerable to so-called side-channel attacks, in which sensitive information can be recovered through the analysis of the leakages produced by the operating device. In the particular case of block ciphers, substitution boxes are often the target of such attacks, as they are the main nonlinear component of the cipher. Literature survey contains some definitions of theoretical properties to measure the resistance provided by substitution boxes with respect to the imminent threat of side-channel attacks. The fundamental questions we board in this paper are: are all these properties related? And if so, what can we tell of their relation? We pretend to bring some clarification to this subject using some well-known side-channel related properties of S-box.